Study on Mechanical Properties of Concrete Contain Untreated and Treated Pineapple Leaf Fiber - SORANI, SITI IZZATUL AISYAH BT MOHD SORANI; BINTI A RAHMAN, NOOR KHAZANAH; BINTI TUAN ISMAIL, TUAN NOOR HASANAH (Progress in Engineering Application and Technology, 2022)
Concrete made from recycled resources is becoming widespread, competing with standard composites. Aside from reducing agricultural waste capacity in landfills, this has indirectly succeeded in generating new methods to address resource exploitation in construction. Agricultural waste may be used as a concrete fiber, addition, or filler. Pineapple leaf fiber is a novel source of steel for concrete. Thus, this study compares the tensile strength of PALFs treated with different sodium hydroxide solutions (5, 7, and 10%) to those left untreated. A Universal Testing Machine will test each specimen’s tensile strength (UTM). It compares the tensile and compressive strength of PALF to regular concrete, with a maximum proportion of 10% being utilized. The compressive and tensile strengths of PLAF and concrete are studied. PALF is added in percentages of 0.1, 0.2, and 0.3 percent to the concrete’s constituent volume weight (by volume). In a cube mold, the mixture is separated into 24 cubes and 12 cylinders. They will be evaluated in the lab for 7 days starting on day 28. Cubes are evaluated for compression and tensile strength. On day 28, the cube specimens treated with 0.2 percent PALF had the greatest compressive (30.05 MPa) and tensile (2.700 MPa) strengths. It may help enhance compressive and tensile strength beyond concrete.